Oil supply risk and affecting parameters associated with oil supplementation and disruption. (10th May 2020) - Iqbal, Wasim; Fatima, Arooj; Yumei, Hou; Abbas, Qaiser; Iram, Robina
Abstract: The fossil fuel energy carriers significantly affect the energy security. The oil security has turned to one of the main political agenda by considering the two world's oil crises. In this study, an index of oil supply vulnerability has been developed to compare the world's top fifteen oil importing South Asian countries. The index includes comprehensive set of indicators like imported oil over GDP ratio, market liquidity, GDP per capita, geopolitical risk, diversification, the ratio of oil importation over consumption, transportation risk, oil price volatility and US volatility. Two popular techniques (composite indicator (CI) and the principal component analysis (PCA)) were used to combine all the aforesaid indicators. Although numerous techniques have been used to assess the oil vulnerability index, for example DEA like models and Markowitz theory of portfolio, none of them incorporated the principal component analysis and composite indicator together to develop an oil vulnerability index. Results shows that the South Asian countries have highest economic, supply and overall oil vulnerability risk whereas the second group countries Belgium, Thailand, Spain, Netherlands, Japan, Korea, India and China are in a relatively less risky as compared to South Asian countries. Contrary to this third group of countries are Canada, Singapore, UK, and France, Italy, Germany and US are considered as a least vulnerable country. Highlights: Oil supply security has been assessed. Mathematical compositor indicator has been developed. Oil vulnerability index has been developed. Considerable differences have been resulted among different oil producer and oil consumer countries.